Comparison of Two River Segmentation Methods in Determining Their Restoration Potential - Erdei, Tímea; Boromisza, Zsombor; Domokos, Endre; Dávid, Szilvia (Polish Journal of Natural Sciences, 2023)
The aim of the study was to determine the restoration potential of urban river reaches with two different river segmentation methods. The first method was the evaluation of sections with similar characteristics, delineated before assessment. The second method was the assessment of 100 meter [m] long sections. The method of preliminary sections based on the results can be used if it is possible to delimit sections with similar characteristics from most evaluation criteria. While in cases where several different evaluation criteria are applied, the delimitation of shorter sections with the same length can give good results. From the point of view of the plan to be developed, the method of identifying sections with similar characteristics can play a greater role in delineating the most important restoration sub-goals and their target areas. While the method of shorter sections of the same length can be well-used in the development of more detailed concepts or plans. In addition, the territorial scale is also important. In small areas, on shorter river reaches, the method of short, 100 m long sections can also be used. However, it is better to delimit sections with similar characteristics on a large scale or if field surveys cannot be carried out along the entire section length.